Management of Implementing the Independent Learning Curriculum: Linking and Matching Vocational High School with IDUKA - Sulistio Sulistio; Yuniarto Mudjisusatyo; Arif Rahman (RIRAI Publisher, 2024)
The research is aimed at: analyzing the head of the study program and productive teachers in the analysis of basic competencies according to the needs of IDUKA; analyzing the concept of application of independent curriculum learning according to IDUKA's needs; and analyzing industrial work practices following a prakerin program at IDUKA for at least 6 months. This research uses qualitative research models with descriptive methods. The data analyzed is data from interviews, research papers, observations, and making field records with the Head of State Vocational Education of 1 Lima Puluh, Head of Multi Media Studies Program, Chair of Hospitality Study Program, Chief of Program Studies of Crafts, Deputy Head of School Curriculum, and Teacher of Lectures related to the Management of Application of Curriculum Merdeka Learning Through Link and Match The results obtained from this research are: (1) The efforts made by the Head of the School have reached the Planning and Implementation Stage; (2) proof of the MOU/MOA already done by 3 entrepreneurs relevant to the skill and competence of the student as a place to test the competence of the place of the CPL/student; (3) teachers create an active learning atmosphere; (4) conduct practical activities; (5) facilitate additional information from the Internet and Platform of Enterprises, seeing the latest developments and trends; and (6) link and match with IDUKA with practical modules relevant to industry needs.